The new species of the genus Atanygnathus Jacobson, 1909 (Coleoptera: Styphylinidae: Staphylininae) from Réunion Island - Kocian, Matúš; Hlaváč, Peter (Zootaxa, 2019)
New species Atanygnathus poussereaui Kocian & Hlaváč, sp. n. from Réunion is described and illustrated. Key to all species of Atanygnathus (Coleoptera, Staphylinidae, Staphylininae, Tanygnathinina) of Réunion is presented.